The Influence of Survey, Question, Read, Reflect, Recite, and Review (SQ4R) Strategy on Elementary School Students' Sight Reading Skills - Hendrizal, Hendrizal; Bismi, Bismi; Islamidar, Islamidar; Andriasari, Septi; Irdawati, Irdawati (Widyagogik, 2025)
The problem in this research is that elementary school students' sight reading skills are still not optimal. The reason is that in skim reading skills, students are less motivated to read the text, students have difficulty understanding the content of the text, and students have difficulty in concluding the content of the text. Students' lack of motivation in sight reading is one of the factors that causes students' sight reading skills to not be optimal. This research aims to determine whether there is an influence of the SQ4R) strategy on students' skim reading skills in elementary schools. This type of research is Quasi Experimental Design with a Nonequivalent Control Group Design research design. The population of this study were elementary school students with the sampling technique being random sampling. Data obtained with the final test were analyzed using the t test. The results of the research using normality and homogeneity tests on both data were normally and homogeneously distributed. Next, a hypothesis test was carried out with the t-test showing tcount= 3.731 and ttable= 1.688 with df= 38 (n1 + n2 – 2 = 19+19-2=36) and a significance level of 5%. Based on testing tcount ttable (3,731 1,688), H0 is rejected and H1 is accepted with the conclusion that there is an influence of the Survey, Question, Read, Reflect, Recite, and Review (SQ4R) strategy on students' short- online reading skills in elementary schools.